A case report of drug–drug interaction between voriconazole and simnotrelvir/ritonavir - Chen, Tingting; Zhang, Qingquan (Frontiers in Antibiotics, 2025)
Co-administration of simnotrelvir/ritonavir with voriconazole should be avoided, as stated in the product insert of simnotrelvir/ritonavir, due to the anticipated decrease in the plasma concentration of voriconazole. Currently, there are no published reports regarding a pharmacokinetic interaction between simnotrelvir/ritonavir and voriconazole. We present the case of an 88-year-old man with pulmonary aspergillosis and coronavirus disease 2019 (COVID-19) co-infection treated concurrently with voriconazole and simnotrelvir/ritonavir. Prior to initiating simnotrelvir/ritonavir, two trough concentrations of voriconazole were measured, yielding values of 2.8 and 2.6 mg/L. After 2 days of co-administration with simnotrelvir/ritonavir, the voriconazole trough concentration rose to 6.0 mg/L. The voriconazole dose was subsequently reduced by 25%, and simnotrelvir/ritonavir was discontinued after completion of the standard 5-day course. A week after voriconazole dose reduction (4 days after simnotrelvir/ritonavir withdrawal), the trough concentration was measured again and was found to be 3.5 mg/L. This case indicates that the trough concentration of voriconazole increased significantly during co-administration with simnotrelvir/ritonavir. Moreover, the interaction persisted even after discontinuation of simnotrelvir/ritonavir, necessitating dynamic dose adjustments guided by therapeutic drug monitoring.